2014
DOI: 10.1097/jnn.0000000000000095
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Behaviors and Illness-Related Factors as Predictors of Recurrent Headache in U.S. Adolescents

Abstract: Providing evidence to clinicians that lifestyle behaviors and illness-related factors are associated with adolescent headache may improve overall headache assessment and may result in a more comprehensive plan of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 148 publications
(362 reference statements)
1
17
1
Order By: Relevance
“…Walter [ 33 ] found that lifestyle behaviours such as skipping meals, water intake, tobacco and alcohol use, and physical inactivity predicted recurrent headache. The SNs in this study found that adolescent inactivity and extensive use of social media were related to headaches, neck, back, and shoulder pain, as well as sleep problems, all of which are confirmed by previous research [ 1 , 10 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Walter [ 33 ] found that lifestyle behaviours such as skipping meals, water intake, tobacco and alcohol use, and physical inactivity predicted recurrent headache. The SNs in this study found that adolescent inactivity and extensive use of social media were related to headaches, neck, back, and shoulder pain, as well as sleep problems, all of which are confirmed by previous research [ 1 , 10 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 26% of the adolescents experienced recurrent headaches. Overall, smoking regularly defined as at least one cigarette daily for 30 days did not have a significant main effect with headache (OR 1.15, 95% CI 0.97‐1.4) or any age group, although the effects were significant for Hispanics ( P = .0023) with customized odds ratios that were double …”
Section: Supporting Smoking Studiesmentioning
confidence: 90%
“…Overall, smoking regularly defined as at least one cigarette daily for 30 days did not have a significant main effect with headache (OR 1.15, 95% CI 0.97-1.4) or any age group, although the effects were significant for Hispanics (P = .0023) with customized odds ratios that were double. 89 Headache Currents 7 | Headache | 2015 1034 | Headache | July/August 2015 A 2014 study available in abstract only used a selfadministered questionnaire with 1876 students attending 18 secondary schools in 10 cities of Croatia. Migraine prevalence was 12.8%.…”
Section: Adolescents and Childrenmentioning
confidence: 99%
“…27 To avoid this annoyance which generally appears mid-morning and to ensure an energy reserve, it is advisable not to neglect breakfast, which must be complete, combined with coffee, tea or milk, biscuits, rusks, and jam or fruit juices. 28…”
mentioning
confidence: 99%